Plasticity in Cell Division Patterns and Auxin Transport Dependency during in Vitro Embryogenesis in Brassica napus . Issue 6 (20th June 2014) - Soriano, Mercedes; Li, Hui; Jacquard, Cédric; Angenent, Gerco C.; Krochko, Joan; Offringa, Remko; Boutilier, Kim
Abstract : This study shows that two patterning pathways can operate during in vitro embryogenesis: a zygotic-like pathway driven by the suspensor, characterized by more regular cell division and a requirement for polar auxin transport to establish the embryo proper, and a suspensorless pathway, characterized by less regular cell division and no requirement for auxin transport. Abstract: In Arabidopsis thaliana, zygotic embryo divisions are highly regular, but it is not clear how embryo patterning is established in species or culture systems with irregular cell divisions. We investigated this using the Brassica napus microspore embryogenesis system, where the male gametophyte is reprogrammed in vitro to form haploid embryos in the absence of exogenous growth regulators. Microspore embryos are formed via two pathways: a zygotic-like pathway, characterized by initial suspensor formation followed by embryo proper formation from the distal cell of the suspensor, and a pathway characterized by initially unorganized embryos lacking a suspensor. Using embryo fate and auxin markers, we show that the zygotic-like pathway requires polar auxin transport for embryo proper specification from the suspensor, while the suspensorless pathway is polar auxin transport independent and marked by an initial auxin maximum, suggesting early embryo proper establishment in the absence of a basal suspensor. Polarity establishment in this suspensorless pathway was triggered and guided by rupture of the pollen exine. Irregular division patterns did not affect cell fate establishment in either pathway. These results confirm the importance of the suspensor and suspensor-driven auxin transport in patterning, but also uncover a mechanism where cell patterning is less regular and independent of auxin transport.